2014
DOI: 10.2337/db14-0144
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6, a Novel Player in the Pathogenesis of Diabetes

Abstract: Enhanced oxidative stress contributes to the pathogenesis of diabetes and its complications. Peroxiredoxin 6 (PRDX6) is a key regulator of cellular redox balance, with the peculiar ability to neutralize peroxides, peroxynitrite, and phospholipid hydroperoxides. In the current study, we aimed to define the role of PRDX6 in the pathophysiology of type 2 diabetes (T2D) using PRDX6 knockout (2/2) mice. Glucose and insulin responses were evaluated respectively by intraperitoneal glucose and insulin tolerance tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 50 publications
5
71
0
Order By: Relevance
“…Evidence has shown opposite changes of two peroxiredoxin family members in islet cells of insulin resistant mice. Where PRDX3 was reduced, which is consistent with the protective role of this protein, but PRDX6 was increased . Here, it is possible that PRDX1 was up‐regulated by other stimulatory molecules to maintain a redox state of mitochondrial and protect the development of overt diabetes .…”
Section: Discussionsupporting
confidence: 63%
“…Evidence has shown opposite changes of two peroxiredoxin family members in islet cells of insulin resistant mice. Where PRDX3 was reduced, which is consistent with the protective role of this protein, but PRDX6 was increased . Here, it is possible that PRDX1 was up‐regulated by other stimulatory molecules to maintain a redox state of mitochondrial and protect the development of overt diabetes .…”
Section: Discussionsupporting
confidence: 63%
“…However, islet cells showed increased PRDX6, another antioxidant member of the Peroxiredoxin family known (as for PRDX3) to be down-regulated by inflammation 38b,39 . It is possible that PRDX6 is upregulated by other stimulatory molecules to restore a mitochondrial redox state and protect the mice from developing overt diabetes 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Prdx6 expression, localization, and protective function have also been shown in mitochondria (20), endoplasmic reticulum (ER) and lysosomal organelles (58,59), and plasma membrane (1). Loss of Prdx6 causes etiopathogenesis in many type of tissues and organisms, leading to such conditions as diabetes and neuronal cell degeneration, while introduction of Prdx6 reverses or delays the process (20,43,47,57). In the current study, we demonstrated that human and mouse neuronal cells, HCN-2 and HT22, are susceptible to oxidative stress from paraquat, glutamate, or H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%